STUDYING, PRESERVING, AND PROMOTING HISTORICAL AND CULTURAL HERITAGE IN THE KHOREZM REGION AND ADDRESSING INTERNATIONAL COLLABORATION ISSUES (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
In the article is discussed issues of international cooperation in the process of studying, restoration and popularization of historical and cultural monuments of the Khorezm oasis and emphasizes that the main place is occupied by the work carried out by the UN organization UNESCO.